Improvement of Microstructure and Properties of Q235 Steel by Iron-Based Laser Cladding Coating - Yuanwei He; Yu Gu; Li Tang; Hu Wang (Advances in Materials Science and Engineering)
Laser cladding is a repair and surface-strengthening technology for the protection of metal parts. It is an effective method for improving the properties of various metal substrates. The process involves melting and solidifying alloy powder on the surface of the substrate. The aim of the present study was to explore the effect of iron-based alloy laser cladding coating on Q235 substrate. Three types of specimens were obtained from Q235 base material using a 5 kW cross-flow CO2 laser beam. Sample 1 and sample 2 were obtained by the addition of rosin to the iron-based alloy powder. Sample 3 was obtained through the addition of rosin and vanadium to the iron-based alloy powder. A gas curtain was used to wrap the molten pool of samples 2 and 3. The surface hardness of the specimens was determined using a Rockwell hardness tester, and the tensile strength was evaluated using the universal mechanical testing machine. The microstructure of the cladding coating was explored using an Olympus optical microscope and SEM. The results showed that the average hardness of sample 2 and sample 3 was 6.42% and 19.84% higher than that of sample 1. The average tensile strength of samples 2 and 3 was 7.42% and 10.37% higher than that of sample 1. The grain of sample 3 was finer than that of sample 2, and that of sample 2 was finer than that of sample 1 under the same magnification. Rosin minimized oxidation of the substrate, whereas the gas curtain prevented the entry of air into the molten pool, hence the improved properties of samples 2 and 3 compared with that of sample 1. Rosin and the gas curtain protected the powder from oxidation loss and improved the quality of the cladding coating. The results of the present study show that rosin reduced the oxidation of iron-based powder, whereas vanadium improved the hardness and strength of the substrate as well as refined the grain size.